Characterisation of the role of TLNRD1 in vascular development and integrity in zebrafish - Berki, Bence (My University, 2022)
Angiogenesis, the formation of new blood vessels, is an essential process for vascular growth and blood vessel development. Defective regulation and abnormalities of angiogenesis are present in multiple diseases, such as cancer, diabetes, arthritis, psoriasis and many others. Angiogenesis utilizes multiple mechanisms, such as sprouting of new veins, vascular remodelling, tumour mediated trans-differentiation and vascular mimicry. In this research project, we focus on sprouting angiogenesis, filopodia and interacting proteins, which aid in the process of angiogenesis. Talin rod domain-containing protein 1 (TLNRD1) is a small protein which shares homology with a major cytoskeletal protein Talin. Especially the domains R7 and R8 of Talin are most similar with TLNRD1. When comparing the genes encoding these domains, the area encoding domains R7 and R8 has 11 exons, but the gene encoding TLNRD1 consists from one single exon. This indicates that tlnrd1-gene is conserved in evolution, which is common for many important genes in cellular functions. TLNRD1 shares also the ability to bind and bundle actin with regular Talin, which is necessary for filopodia formation and it is linked with sprouting angiogenesis. The goal of this research project was to shed light on this role of TLNRD1, by using a zebrafish model. The common zebrafish (Danio rerio) is a vastly used animal model in vascular growth and cancer research. For this project, a transgenic strain of TLNRD1 mutant fish was produced prior the project. TLNRD1-mutant embryos were produced and imaged with a stereo microscope for observing structural differences in their vasculature. The lengths and diameters of blood vessels were measured and analysed statistically. Genotyping was done with PCR and gel electrophoresis. Within the naturally spawned embryos, no significant differences were observed between the control and mutant groups. Visual phenotype related observations of abnormalities or vasculature changes were also quite minuscule. In the second phase of the experiment, microinjections with CRISPR-CAS9 and single guide RNAs were conducted, to find out how the gene edition of TLNRD1 effects on the phenotype. Recently fertilized embryos were injected, cultured and imaged again. Due to using CRISPR for gene editing, instead of regular genotyping a T7 endonuclease assay was conducted to measure the gene edition. In addition, a database search of RNA expression patters of TLNRD1 was conducted using the UCSC Cell Browser and a high-profile transcriptional RNA dataset of zebrafish. The conclusion of this project was that although TLNRD1 has previously been shown to affect vascular development, no major significance or visual phenotype differences were observed among the target embryos. Possible reasons could be the somewhat low levels of initial expression of TLNRD1 or the actual significance of the protein being smaller in vascular development than previously anticipated.
Keywords: angiogenesis, zebrafish, microinjection, CRISP-Cas9